Digital Learning and Teacher Motivation’s Impact on Student Satisfaction and School Competitive Advantage - Dewi, Arinta; Sutjipto, Mohammad Riza (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
In today's era of rapid educational transformation, the integration of digital technology in learning is a key factor in improving the quality of educational services. This is also the case at Putera Harapan Purwokerto 3 Language School (Puhua School) which also faces the challenge of maintaining and improving the quality of learning experiences where in the current era, students are increasingly demanding learning experiences that are adaptive, interesting and relevant to the needs of the times. This is important for the competitiveness of educational institutions in the current era. This study aims to analyze the effect of digital learning and teacher motivation on student satisfaction and its implications for the school's competitive advantage, with a case study at SMP-SMA 3 Bahasa Putera Harapan (Puhua School) Purwokerto. Various literatures reviewed and become the foundation of the framework in this study such as customer satisfaction theory, work motivation, as well as competitive advantage from Porter and two-factor theory show that effective digital learning can improve the quality of students' learning experience, especially if it is supported by high teacher motivation. Student satisfaction is positioned as a mediating variable that connects the influence of digital learning and teacher motivation on school competitiveness. The research method used is a quantitative approach with the SEM-PLS model, accompanied by qualitative validation through in-depth interviews. Data were collected from students and teachers using random sampling technique and analyzed using SmartPLS. The analysis technique used is path analysis to test the direct and indirect relationships between variables. The results show that digital learning and teacher motivation have a positive effect on student satisfaction. Student satisfaction is also proven to have a significant effect on the school's competitive advantage. In addition, student satisfaction mediates the relationship between digital learning and teacher motivation to competitive advantage. The simultaneous effect of the two independent variables also showed significant results in improving school competitiveness through student satisfaction. Data triangulation results show that both approaches are mutually reinforcing and consistent where all quantitative findings are qualitatively confirmed and no significant contradictions are found. In conclusion, the synergy between the implementation of digital technology and high teacher motivation is an important strategy in building student satisfaction and strengthening the school's competitive position. Schools are advised to continue developing digital learning systems and teacher motivation enhancement programs to meet future educational challenges.